Karakteristik Subrogasi pada Penyaluran Kredit Usaha Rakyat dalam Perspektif Hukum Perdata - Eriza Izzati; Catherin Ariyanto; Nabillah Fitria Nugraha; Althea Salza Nastiti (Faculty of Law, Maranatha Christian University, 2023)
Government creates various programs in order to achieve public welfare. One of them is Kredit Usaha Rakyat, a micro credit program, through which micro, small, and medium-scale enterprises (MSMEs) are expected to strengthen their capital. The distribution mechanism of KUR appears to indicate a subrogation pattern. The term subrogation refers to substitution of creditors by a third party, consequently creating a new party and affecting the KUR agreement. Grounded from this phenomenon, this work aimed to find out the legal relationship among creditors, debtors, and insurance companies in respect to KUR distribution and to find out the legal consequence of subrogation in KUR. To this end, a normative legal study with statute and conceptual approaches was conducted by reviewing and prescriptively analyzing relevant literature. The finding showed that subrogation pattern in KUR distribution did not comply with the subrogation principle regulated in the Indonesian Civil Code, as it did not annul the old agreement between the debtor and creditor and created new arrangement between the debtor, creditor, and the third party (insurance company). In other words, KUR distribution does not implement subrogation as the old arrangement between the debtor and creditor is not void when an insurance company warrants the debtor's debt to the creditor.